Effect of flaxseed supplementation on metabolic profile and reproductive performance of prepubertal gilts - SINGH, A K; SINGH, U; SHARMA, A; KAUR, P; SINGH, P (The Indian Journal of Animal Sciences, 2021)
This study was conducted on Large White Yorkshire prepubertal gilts (n=36) to evaluate the effect of flaxseed supplementation on feed intake, bodyweight, metabolic profile and reproductive parameters. The gilts were randomly allocated to three treatments, viz. group 1 (n=12; control), group 2 (n=12) and group 3 (n=12). All gilts received grower-finisher rations, twice daily from 120 days of age until 240 days of age. Additionally, in group 2 and group 3, flaxseed was mixed at a rate of 0.5% and 1.0% of dry matter, respectively. Average daily feed intake did not differ between three groups. Bodyweight and daily bodyweight gain were more in gilts of group 3 than in group 2 and group 1 toward the end of feeding period. The gilts of group 3 had an improved feed conversion ratio compared to their contemporary mates throughout the study period. Over the period of time, a significant reduction in cholesterol levels and linear increase in IGF-1 levels was noticed in gilts of group 3 as compared to their counterparts. Gilts of group 3 reached puberty and expressed estrus at breeding significantly earlier than in their contemporary mates. The number of total piglets born and born alive was maximum in group 3 followed by group 2 and group 1. Piglet birth weight and still birth percentage were similar in all groups. In conclusion, supplementing flaxseed (1.0%) in diet improved body composition variables, age at onset of puberty and reproductive performance of prepubertal gilts.